Efficacy of anti‐fungal agents for invasive fungal infection prophylaxis in liver transplant recipients: A network meta‐analysis. Issue 10 (4th August 2022) - Liu, Yusi; Lan, Chunhai; Qin, Sibei; Qin, Zhuo; Zhang, Zhiqiang; Zhang, Peng; Cao, Weiling
Abstract: At present, there is still a lack of effective invasive fungal prophylaxis therapy in liver transplant recipients (LTRs). This study aimed to analysis the latest evidence on efficacy of current prophylactic anti‐fungal therapy, and systematically compare between anti‐fungal agents and placebo by a fixed‐effects meta‐analysis in all randomised controlled trials. A network meta‐analysis was performed for invasive fungal infection (IFI) among different agents in 14 randomised controlled trials, in which 10 anti‐fungal approaches were identified. Overall, anti‐fungal prophylaxis reduced the rate of IFI (RR 0.30, 95% CI 0.18–0.52) and proven IFI (RR 0.27, 95% CI 0.14–0.53) when compared to placebo. In the network meta‐analysis, an equivalent reduction in the rate of IFI was observed in fluconazole (OR 4.70, 95% CI 1.22–18.10), itraconazole (OR 5.82, 95% CI 1.10–30.71) and Liposomal amphotericin B (LAmB, OR 5.74, 95% CI 1.29–25.58) groups when compared with placebo. Anidulafungin might be the most effective agents in IFI prevention; however, this superiority did not meet statistically significance. Our study indicated that fluconazole, echinocandins and LAmB are equivalent in efficacy. Of which, fluconazole is recommended for the prevention of IFI in LTRs due to its efficacy, economics and compliance.